Occurrence and Morphology of Crayback-like Stalagmites in the Painted Cave of Niah (Sarawak, Malaysia) - Dodge-Wan, Dominique; Deng, A.; Abbas, M. (Springer, 2012)
The Painted Cave is a sub-horizontal relict tunnel passage which runs through a small karst tower, approximately 30 m above the surrounding alluvial plain and adjacent to other large karst towers in Niah National Park (Sarawak, Malaysia). Lundberg and McFarlane (Int J Speleol 40(1):39–43, 2011) described the occurrence, morphology and mode of formation of a crayback stalagmite close to the north entrance of the cave. The presence of numerous other crayback-like stalagmites in three zones of the same cave is reported here. Their elongated humped-back morphology indicates formation influenced by cave wind. The axial orientations of the crayback-like stalagmites are similar in each of the three cave zones, but differ between the zones. Many of the stalagmite features resemble those of crayback stalagmites, suggesting that cyanobacteria may also have played a role in their formation. The Painted Cave has large entrances at both ends. The natural light levels within the cave are sufficient for cyanobacterial growth and cave wind is noticeable. A suite of stalagmite morphologies ranging from forms that are wind influenced but abiotic, to forms that are also moderately to strongly influenced by cyanobacteria is suggested.